THE PRINCIPLE OF JUSTICE IN THE DISTRIBUTION OF SURPLUS RESULTS OF THE EMPLOYEES COOPERATIVE - Qodriyah Isniyati; Danang Wahyu M; Mukti Fajar ND (Awang Long Law Review, 2026)
This study aims to analyze the distribution of the Surplus of Business Results (SHU) of the Employees Cooperative of Universitas Muhammadiyah Yogyakarta in light of the principle of justice. Based on Law Number 25 of 1992 on Cooperatives, Article 45 stipulates that the surplus of business results, after the allocation of reserve funds, shall be distributed to members in proportion to the business services conducted by each member with the cooperative, and shall also be allocated for cooperative education and other cooperative needs in accordance with the decisions of the members meeting. In practice, SHU distribution is generally carried out during the annual members meeting, where members with larger loan amounts tend to receive a greater share of SHU than members with equivalent savings. The principle of justice in SHU distribution is thus oriented toward members who contribute the most significant reserve funds. This research employs a juridical method with a normative approach. The novelty of this study lies in its examination of the application of the principle of justice in the distribution of SHU within the Employees' Cooperative of Universitas Muhammadiyah Yogyakarta. The findings indicate that SHU distribution prioritizes members with the largest loans, resulting in greater SHU benefits than those from savings. However, this practice raises concerns about members' understanding of justice, as many perceive fair distribution as equal allocation among members. Therefore, cooperative management should be more proactive in disseminating cooperative literacy to ensure that members do not perceive the differences in SHU allocation as "unfair". Aristotle conceptualized justice as a balance between numerical equality and proportional equality, namely granting rights in accordance with capacity and merit, which aligns with the application of SHU distribution in the Employees' Cooperative of Universitas Muhammadiyah Yogyakarta.